How Effective Is Central Bank Forward Guidance? - Clemens J. M. Kool; D.L. Thornton (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2012)
In this paper, we use survey forecasts to investigate the impact of forward guidance on the predictability of future short- and long-term interest rates in four countries: New Zealand, Norway, Sweden, and the United States. New Zealand began providing forward guidance in 1997, Norway in 2005, and Sweden in 2007. The United States had two periods of implicit forward guidance: 2003-2005 and 2008-2011. Overall, we find little or no convincing evidence that forward guidance actually improves markets' ability to forecast future rates or that any improvement in forecasting short-term rates is reflected in longer-term yields. The weak support we do find is at the short end of the yield curve and at relatively short forecast horizons and only for Norway and Sweden. There is no evidence that forward guidance has increased the efficacy of monetary for New Zealand, the country with the longest–15-year–forward guidance history.
Keywords: 330; monetary policy; central bank transparency; interest rates; term structure; forecasting